Genomic Investigation of Proteus mirabilis Isolates Recovered From Pig Farms in Zhejiang Province, China - Qu, Xiaoyun; Zhou, Jie; Huang, Haoqi; Wang, Wen; Xiao, Yingping; Tang, Biao; Liu, Hanlin; Xu, Chenggang; Xiao, Xingning (Frontiers in Microbiology, 2022)
Proteus mirabilis is a common opportunistic zoonotic pathogen and its ongoing acquisition of antimicrobial resistance genes poses challenges to clinical treatments. Human-sourced whole genomic sequencing of human P. mirabilis isolates have been reported but pig-sourced isolates have not been thoroughly investigated even though these animals can serve as reservoirs for human infections. In the current study, we report a molecular epidemiological investigation to unravel the antimicrobial and virulence gene risk factors for P. mirabilis contamination in 9 pig farms in 3 different cities in Zhejiang Province, China. We collected 541 swab samples from healthy pigs and 30 were confirmed as P. mirabilis. All 30 isolates were resistant to tetracyclines, macrolides, sulfonamides, β‑lactams and chloramphenicol and all were multiple drug resistant and 27 were strong biofilm formers. Phylogenetic analyses indicated these 30 isolates clustered together in 2 major groups. Whole genome sequencing demonstrated that the isolates possessed 91 different antimicrobial resistance genes belonging to 30 antimicrobial classes including rmtB, sul1, qnrS1, AAC(6')−Ib−cr, blaCTX−M−65 and blaOXA−1. All isolates contained mobile genetic elements including integrative conjugative elements (ICEs) and integrative and mobilizable elements (IMEs). Minimum inhibitory concentration (MIC) testing indicated direct correlates between cognate genes and antimicrobial resistance. We also identified 95 virulence factors and almost all isolates contained 20 fimbrial and flagellar operons and this represents the greatest number of these operon types found in a single species among all sequenced bacterial genomes. These genes regulate biofilm formation and represent a confounding variable for treating P. mirabilis infections. Our P. mirabilis isolates were present in healthy animals and multiple drug resistance in these isolates may serve as a reservoir for other intestinal and environmental Enterobacteriaceae members. This prompts us to more strictly regulate veterinary antibiotic use.